The sequential two photon dissociation of NO as a source of aligned N(D-2), N(S-4) and O(P-3) atoms - Bakker, B; Eppink, A; Parker, D; Costen, M; Hancock, G; Ritchie, G (1998)
Velocity map imaging is used to characterise the angular distributions of atoms which are formed from the sequential two photon excitation of NO via the A2Σ+ state. Molecules excited at 226 nm and dissociated at 339 nm from the same laser source yield two sets of products, ground state O(3P) atoms in conjunction with N(2D) and N(4S). The angular distributions are found to be well described by β parameters. The use of this method as a source of monoenergetic aligned atoms for studies of reaction dynamics is discussed.